Perpindahan Massa Antar Fasa Pestisida Organofosfor Dalam Tanah Sawah - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian UGM, 2005)
ABSTRAK The volumetric interface mass transfer model was more suitable to express interface mass transfer of pesticide at the flooded soil system. Therefore the volumetric interface mass transfer coefficient and the empirical equation of the relationship between the volumetric interface mass transfer coefficient and the affecting variables was studied in this research. The soil was put into a glass column and then compacted, so that the structure became similar with its original soil structure. The glass column was covered with aluminium foil